AN OVERVIEW OF HEMP FIBRE (International Journal of Engineering Sciences & Management Research, 2016)
Sunhemp (Crotalaria juncea, L), a plant of sub-order Paplionaceae of order Leguminoseae is an annual shrub cultivated as multipurpose legume especially for its fine fibre in many countries including India. The crop is also grown for legume or as a fodder. The sunhemp crop is native to India. The crop is known in India by various names like 'Sonai' or 'San' (Hindi), 'Sanpat' (Bengali), 'Tag' (Marathi), 'Vakku' (Malayalam), 'Janumu' (Telegu), 'Saab' (Kannada). Hemp originated in Central Asia where it was cultivated as a fibre and food crop. Hemp, growing in temperate zones, is an annual cultivated from seed, reaching a height of up to 16 feet (5 metres).